Numerical investigation of regeneration process of diesel particulate filter (DPF) made of different constitutive materials - Firat, Mujdat; Coskun, Nevfel Yunus; Okcu, Mutlu; Varol, Yasin (Gazi Univ, Fac Engineering Architecture, 2019)
Diesel Particulate Filters (DPF) are currently used in many diesel vehicles. In this study, the filtration characteristics of different DPF materials including SiC. Crd and AT were investigated under the New European Driving Cycle (NEDC) standards by designing the exhaust system for a diesel vehicle with Diesel Oxidation Catalyst (DOC) and DPF. The exhaust system model is determined by examining of the diesel vehicles. The study was performed in three dimensions with using of the AVL-FIRE software. The properties of materials which are alternatives to SiC (Silicon Carbide), the most widely used as DPF material, have been investigated. The effects of DPF material on heat transfer, pressure drop and exhaust emissions were shown in this study. As a result, it is seen that the used materials in this study have similar characteristics on the studied parameters. However. DPF materials have been found to have effects on pressure drop. CO and NOx. For DPF with SiC material, thermal losses are high at the beginning of regeneration. CO emissions are low when the AT (Aluminum Titanate) material used, and pressure drop is high for Crd (Cordierite) material.
Farklı malzemelerden yapılmış Dizel Partikül Filtresi (DPF)’nin rejenerasyon sürecinin sayısal olarak incelenmesi
Keywords: Diesel particulate filter; regeneration; exhaust emissions; heat transfer